Brazilian consensus of specialists on the diagnosis of attention-deficit/ hyperactivity disorder in adults - Mattos, Paulo (2006)
Present difficulties in the diagnosis of attention-deficit/hyperactivity disorder in adults have prompted Brazilian specialists involved in research in this area to make a consensus to be used in the country. A non-systematic preliminary review was repeatedly evaluated by all authors, who added new material, commented and corrected parts of the text for 6 months through electronic mail and a further meeting sponsored by the Brazilian Association of Attention-Deficit Disorder. The preliminary version was publicly presented during the annual congress of the Associação Brasileira de Psiquiatria (Brazilian Association for Psychiatry) for appraisal and suggestions from participants in order to prepare the final version. Copyright © Revista de Psiquiatria do Rio Grande do Sul - SPRS.